Teachers’ Competence: Are Educational Background and Training Had Significant Effect? - Mohamad Arief Rafsanjani (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aims to look into theories about teacher competency, educational background, and training, where the hypothesis claims that educational background and training involvement has a positive link with teacher competence. This is an explanatory study that seeks to explain the relationship between characteristics such as educational background, participation in training, and teacher competency. With 35 samples, this study was conducted on economic teachers at Malang Senior High School. Regression was employed in the data analysis. According to the findings of this study, there is no strong indication that teachers' educational background and training influenced their ability. This study was unable to demonstrate a beneficial relationship between educational background, training involvement, and teacher competency.